Archery fundamentals - Johnson, Teresa 1977- (Human Kinetics, 2015)
Archery is one of the hottest sports out there, and there's no better introduction to the sport than Archery Fundamentals, Second Edition. Inside are all of the essentials you need to succeed and get on target. Instructions and photographs guide you through every step of the process of becoming an archer, from stringing your bow to learning basic shooting technique. You'll also find insider tips for choosing, adjusting, and maintaining archery equipment as well as recommendations to improve your accuracy. You'll discover how to correct errors and fine-tune your approach. And, if you want to compete, you'll appreciate the how-tos for taking part in archery tournaments